Raqib in Kurdish Classical Poetry (Poems of Nali, Saleem, Kurdi, Mahvi for example) - Abdalla, Mohamed Amin (Sulaimani Journal for Humanities, 2019)
The present study is entitled “The Antagonist in the Classical Kurdish Poetry: Nali, Salim, Kurdi and Mahwi as examples. It explores the concept of ‘the protagonist’ which is common in classical Kurdish poetry where it was applied to someone whom the poet regarded as his opponent and thus attacked and disparaged in his poems. In our study, however, we have developed an opposite view on the matter by investigating into the poems of the four poets Nali, Salim, Kurdi and Mahwi and have arrived at the conclusion that the protagonist is not necessarily a scoundrel or a disfavored person which the poet usually describes. Rather, the protagonist is the one who is close to the sweetheart and with whom the sweetheart wants to have an intimate relation with. Thus, the poet himself appears between his sweetheart and the other male person (whom he calls the protagonist) and dislikes the fact that his sweetheart loves him too. This means that since the poet himself is the speaker in the poems, he exchanges his and his protagonist’s position regularly. Accordingly, we have worked on assigning each his own position with regard to the loved one.